Problematic issues of current liabilities accounting and ways to solution (Economics and region, 2023)
The article specifies the peculiarities of the organization of accounting of current liabelities at branches that are part of Joint stock company "Ukrainian railway". The definition of the group "current liabelities” is given. The main regulations governing the accounting of current liabelities are researched. The article explains that current liabelities will be repaid during the operating cycle of the enterprise or that must be repaid within 12 months starting from the balance sheet date. In addition, it is examined what forms of evaluation are used to classify current liabelities.
Keywords: Joint stock company; current liabelities; the FOBOS automated accounting system; accounting